2011
DOI: 10.1080/17441690903334240
|View full text |Cite
|
Sign up to set email alerts
|

Gender and community views of stigma and tuberculosis in rural Maharashtra, India

Abstract: Stigma associated with tuberculosis (TB) is often regarded as a barrier to health seeking and a cause of social suffering. Stigma studies are typically patient-centred, and less is known about the views of communities where patients reside. This study examined community perceptions of TB-related stigma. A total of 160 respondents (80 men and 80 women) without TB in the general population of Western Maharashtra, India, were interviewed using Explanatory Model Interview Catalogue interviews with same-sex and cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
82
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(93 citation statements)
references
References 20 publications
6
82
0
5
Order By: Relevance
“…The pressures of housework and the strain of secrecy among women were significant obstacles to treatment adherence. Subsequent research in rural Maharashta found similar trends (Atre et al, 2009). Highly dichotomized gender roles throughout Maharashta meant that a diagnosis of TB together with a patient's interaction with the local treatment facility may be a severe challenge to socially acceptable gender practices and culturally assigned gender identities.…”
Section: Gendermentioning
confidence: 89%
See 1 more Smart Citation
“…The pressures of housework and the strain of secrecy among women were significant obstacles to treatment adherence. Subsequent research in rural Maharashta found similar trends (Atre et al, 2009). Highly dichotomized gender roles throughout Maharashta meant that a diagnosis of TB together with a patient's interaction with the local treatment facility may be a severe challenge to socially acceptable gender practices and culturally assigned gender identities.…”
Section: Gendermentioning
confidence: 89%
“…Substantial shortcomings in case-detection are not only due to the limitations in available diagnostic strategies and time-consuming laboratory tests (Pai et al, 2012;Engel & Pai, 2013). Barriers to diagnosis and treatment also include geographical challenges, economic difficulties, communication issues (Chemtob et al, 2000), fears of stigma (Nair et al, 1997;Coreil et al, 2010), unregulated private health care practices (Bhargava et al, 2011), non-adherence to treatment (Greene, 2004) and gender biases in health-seeking behaviour (Wang et al, 2008;Atre et al, 2009). Often left to operate at an intuitive level, perspectives from the humanities and social sciences contribute significantly to tackling the problem of TB by providing conceptual tools to pay attention to complexity, question the familiar, reconfigure boundaries to create novel frameworks and to critically examine assumptions, arguments and false reasoning (Porter, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In a study conducted to find out the community's perception of the disease "fear of losing social status, marital problems and hurtful behaviour by the community" were perceived as common reasons for concealing the disease. 64 Stigma continues to be a cause for delay in seeking treatment and both males and females continue to carry a "psychological burden of unfulfilled social responsibilities" due to the disease. 64 Gender is apparently an important determinant of outcomes in TB with females being at considerable disadvantage.…”
mentioning
confidence: 99%
“…64 Stigma continues to be a cause for delay in seeking treatment and both males and females continue to carry a "psychological burden of unfulfilled social responsibilities" due to the disease. 64 Gender is apparently an important determinant of outcomes in TB with females being at considerable disadvantage. Besides more distressing emotional and social symptoms, difficulties in marriage, social isolation, inability to care for children and family etc are some major problems.…”
mentioning
confidence: 99%
“…Recent studies in different settings that have investigated the impact of TB stigma on the lives of patients and family members suggest that this phenomenon is more common in developing countries. 1,2,4, [8][9][10][11][12] Stigma has been associated with lower self-esteem, depression, feelings of being misunderstood and ashamed, poor medication adherence, fewer successful social interactions, reduced help seeking and poor recovery. 2,9,10 Authors have, however, pointed out that social support may be used to tackle the negative effects of stigma and increase the patient's self-esteem, thus increasing adherence to treatment.…”
mentioning
confidence: 99%